The Influence of Social Capital on Entrepreneurial Success - Tewari, Veena; Panicker, Sunita; Eduria, Orlando W.; Kishan, Kanchralapalli; K, Asha S (Journal of Posthumanism, 2025)
Advancing a posthumanist perspective, this study investigates how entrepreneurial success is shaped within digitally networked environments where human and non-human agents intersect. Entrepreneurs increasingly navigate trust and decision-making not only through interpersonal relationships but also via algorithms, AI tools, and platform infrastructures. Using qualitative data from interviews and digital ethnography, supported by statistical tests, the research identifies a shift from conventional social capital to digitally mediated trust dynamics. Results highlight that while bonding and bridging ties remain valuable, platform reputation systems and algorithmic interfaces significantly influence strategic outcomes. Analytical models further confirm the long-run impact of AI integration and platform visibility on entrepreneurial performance. These findings suggest that entrepreneurial ecosystems now operate as hybrid relational networks, necessitating new approaches to support, regulate, and understand venture success in a digital age.